The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/nu15051236
|View full text |Cite
|
Sign up to set email alerts
|

Focusing on Phosphorus Loads: From Healthy People to Chronic Kidney Disease

Abstract: Phosphorus is an essential micromineral with a key role in cellular metabolism and tissue structure. Serum phosphorus is maintained in a homeostatic range by the intestines, bones, and kidneys. This process is coordinated by the endocrine system through the highly integrated actions of several hormones, including FGF23, PTH, Klotho, and 1,25D. The excretion kinetics of the kidney after diet phosphorus load or the serum phosphorus kinetics during hemodialysis support that there is a “pool” for temporary phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 107 publications
0
2
0
Order By: Relevance
“…The FGF23 gene is a member of a large family of fibroblast growth factors [94], which is most associated with the KLOTHO gene in anti-aging processes [95]. A number of publications have examined the relationship of FGF23 and KLOTHO genes in physiological processes and in various diseases [96][97][98][99][100][101][102][103][104]. In this regard, we studied the possible effect of piRNA on the expression of the FGF23 gene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FGF23 gene is a member of a large family of fibroblast growth factors [94], which is most associated with the KLOTHO gene in anti-aging processes [95]. A number of publications have examined the relationship of FGF23 and KLOTHO genes in physiological processes and in various diseases [96][97][98][99][100][101][102][103][104]. In this regard, we studied the possible effect of piRNA on the expression of the FGF23 gene.…”
Section: Resultsmentioning
confidence: 99%
“…A decrease in the synthesis of this protein is observed in patients with CKD, which may underlie diabetes [6][7][8][9]. Mutations in KLOTHO protein are associated with aging and loss of bone mass and phosphorus metabolism [10,11]. Several works are devoted to elucidating the role of KLOTHO in oncological diseases [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that the management of serum P can play a signi cant role in weight loss in individuals and chronic diseases [11,37]. Assessment of serum P levels is essential in patients with hypothyroidism, because elevated serum phosphorus levels may increase the disease complications and be associated with microvascular dysfunction [38], coronary artery calci cation [39], chronic kidney disease [40], and cardiac arrest [41].…”
Section: Discussionmentioning
confidence: 99%
“…One should take into consideration features of lower bone turnover in all of the applied CKD-MBD models. As the hydroxyapatite of the long bones serves as a huge natural reservoir for Pi [48], low bone turnover may predispose the redistribution of Pi to non-skeletal tissues. Myocardium could be prone to Pi accumulation because of the ability of myocytes to accumulate high amounts of this anion, which is necessary to maintain their high-energy metabolism [49].…”
Section: Discussionmentioning
confidence: 99%